MODIFYING BFGS UPDATE FOR UNCONSTRAINED OPTIMIZATION - Mahmood, Saad Shakir (MAGISTRA, 2004)
In this work, we propose the a-BFGS update. We show that under certain circumstance this a-BFGS update corrects the condition number of the Hessain matrix better than the BFGS does. Our numerical result support this claim and also indicate that the a-BFGS update may be competitive with the BFGS update in general. This a-BFGS update can Key words. Unconstrained optimization, Quasi-Newton methods, BFGS update.